DeepSeek and AI innovation : How Chinese universities broke through the glass ceiling of technological advancement - Allen, Ryan (American Journal of STEM Education, 2025)
This essay[1] explores the DeepSeek AI team and their significant contributions to artificial intelligence. Drawing upon the author's expertise in Chinese higher education and global talent recruitment, the analysis challenges the prevailing narrative that technological innovations in China rely on overseas returnees. By analyzing online bios, the essay reveals that most of the DeepSeek team and their advisors were educated in China, illustrating how Chinese universities have advanced beyond the so-called "Glass Ceiling" in cutting-edge technological research. This breakthrough exemplifies the growing capacity of Chinese institutions to foster homegrown innovation in AI.[1] This essay was adapted from a piece originally published on the College Towns website